Law Enforcement Against Online Prostitution Providers In Indonesia And Egypt - Wardah Yuspin; Aya Mohammed Youssef Abd Allah; Kelik Wardiono; Indah Maulani (Muhammadiyah University Press, 2021)
Purpose of the study :Describe the comparison of Online Prostitution Law in Indonesia and Egypt Methodology :Research methodology is qualilative approach with normative legal research. Therefore, in this study, it is preferable to secondary data collected by literature studies. Data that has been processed for further qualitative analysis Results:The results of this study found that the comparison of the two countries has similarities, namely the lack of legislation on online prostitution and the existence of a police specialty that investigates cases of prostitution in Egypt namely